Uji Antioksidan Daun Kokang (Lepisanthes amoena) dengan Metode DPPH: Antioxidant Analysis of Kokang Leaves (Lepisanthes amoena) Using DPPH Method - Siti Anisah Nur Fajriyati; M Arifuddin; Hadi Kuncoro (Proceeding of Mulawarman Pharmaceuticals Conferences, 2021)
Kokang Leaf (Lepisanthes amoena) as a traditional cosmetic for the Dayak Benuaq and Tunjung tribe is very important to be developed in medicine because it is contain secondary metabolites as antioxidants. This research was conducted with the aim of knowing the yield of kokang leaves (Lepisanthes amoena), the profile of TLC, and knowing the fraction with the greatest antioxidants in kokang leaves (Lepisanthes amoena). The research used DPPH, KLT, and yield calculation method. The yield obtained in ethanol extract 96% = 23%; N-Hexan = 9.448%; Ethyl Acetate = 1.37%; Ethanol 70% = 9.95%. TLC test results using N.Hexan : Ethyl Acetate (2: 1) eluent and then sprayed with 10% H2SO4, in 96% ethanol extract there were 7 stains, N-Hexan Fraction 9 stains, Ethyl Acetate Fraction 5 stains, and Ethanol Fraction 70 % 1 stain. The qualitative test results after spraying DPPH on TLC, there were yellow spots on a purple background indicating antioxidant activity. The IC50 results were obtained in 96% Ethanol Extract 6.8171 ppm, N-Hexan Fraction 10.0184 ppm, Ethyl Acetate Fraction 5.0107 ppm, and Ethanol 70% Fraction 24.7343 ppm. Based on the results above, it can be concluded that the ethyl acetate extract has the highest antioxidant activity with 5.0107 ppm being able to inhibit DPPH radicals.